APPLICATION OF GEOMETRIC ALGORITHMS IN CYBER-PHYSICAL SYSTEMS: ENHANCING DESIGN, CONTROL, AND SIMULATION (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
Cyber-physical systems (CPS) integrate computational algorithms, sensors, and physical processes to achieve real-time monitoring, control, and optimization. Geometric algorithms play a pivotal role in these systems, enabling spatial reasoning, path planning, sensor fusion, and structural analysis. This study investigates the application of geometric algorithms in CPS, focusing on design, simulation, and control processes. Using the IMRaD structure, the research combines literature review, case studies of CPS implementations, and algorithmic modeling experiments. Results demonstrate that geometric algorithms improve system accuracy, efficiency, and predictive capability, supporting autonomous operation, real-time decision-making, and process optimization. The discussion examines methodological approaches, computational challenges, and integration with sensor and control frameworks. The conclusion emphasizes the critical role of geometric algorithms in enhancing the functionality, reliability, and innovation potential of cyber-physical systems.